On the finiteness of the discrete spectrum of a 3x3 operator matrix - Rasulov, T. H. (Methods of Functional Analysis and Topology, 2016)
An operator matrix H associated with a lattice system describing three particles in interactions, without conservation of the number of particles, is considered. The structure of the essential spectrum of H is described by the spectra of two families of the generalized Friedrichs models. A symmetric version of the Weinberg equation for eigenvectors of H is obtained. The conditions which guarantee the finiteness of the number of discrete eigenvalues located below the bottom of the three-particle branch of the essential spectrum of H is found.